IMPLEMENTASI MEDIA PEMBELAJARAN AUGMENTED REALITY TERINTEGRASI GOOGLE SITES DALAM PENINGKATAN PEMBELAJARAN IPS PADA TINGKAT SMP - Sari, Jessika Nacha; Safitri, Desy; Sujarwo, Sujarwo (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT The use of augmented reality (AR) in social studies learning integrated with Google Sites is a technological innovation that allows users to view the real world with additional digital elements such as images, text, or 3D objects. This research describes how the application of AR in social studies learning, through Google Sites, provides opportunities for students to access additional information virtually and interactively. This technology is expected to improve the quality of learning, student engagement, as well as learners' understanding of the material presented. The research objective is to analyze the effect of augmented reality integration with Google Sites on students' understanding in social studies learning. The research method used is a literature review (library research), by collecting data from secondary sources in the form of previous research articles. Based on the literature review, an overview of the influence and positive results of the application of this technology in improving the effectiveness of social studies learning is obtained. The integration of AR through Google Sites proved to be one of the innovative solutions to create a more interesting and immersive learning experience for students. ABSTRAK Penggunaan augmented reality (AR) dalam pembelajaran Ilmu Pengetahuan Sosial (IPS) yang terintegrasi dengan Google Sites merupakan inovasi teknologi yang memungkinkan pengguna untuk melihat dunia nyata dengan tambahan elemen digital seperti gambar, teks, atau objek 3D. Penelitian ini menggambarkan bagaimana penerapan AR dalam pembelajaran IPS, melalui Google Sites, memberikan kesempatan kepada siswa untuk mengakses informasi tambahan secara virtual dan interaktif. Teknologi ini diharapkan dapat meningkatkan kualitas pembelajaran, keterlibatan siswa, serta pemahaman peserta didik terhadap materi yang disampaikan. Tujuan penelitian adalah menganalisis pengaruh integrasi augmented reality dengan Google Sites terhadap pemahaman siswa dalam pembelajaran IPS. Metode penelitian yang digunakan adalah kajian literature (library research), dengan mengumpulkan data dari sumber sekunder berupa artikel penelitian sebelumnya. Berdasarkan kajian literatur, diperoleh gambaran mengenai pengaruh dan hasil positif dari penerapan teknologi ini dalam meningkatkan efektivitas pembelajaran IPS. Integrasi AR melalui Google Sites terbukti menjadi salah satu solusi inovatif untuk menciptakan pengalaman belajar yang lebih menarik dan mendalam bagi siswa.